Efektivitas Media Pembelajaran NEARPOD terhadap Kemampuan Berpikir Logis Peserta Didik SMA - Zainab, Siti; Rafiq Badjeber; Riska Elfira (Universitas Pendidikan Mandalika (UNDIKMA), 2025)
This study aims to determine the effectiveness of the Nearpod learning media on students’ logical thinking skills in the quadratic equation topic at MAN 2 Kota Palu. The research employed a quantitative approach with a pretest-posttest control group design. The sample consisted of two classes: an experimental class that received instruction using Nearpod and a control class that received conventional teaching. The research instrument was a logical thinking test administered before and after the treatment. The normality test indicated that the data were not normally distributed; therefore, the Mann–Whitney U test was used for data analysis. The results showed that the Asymp. Sig. (2-tailed) value of the posttest was 0.103 (> 0.05), indicating no statistically significant difference between the two groups. However, the experimental class obtained a higher Mean Rank than the control class, suggesting a descriptive improvement in students’ logical thinking skills. These findings imply that Nearpod provides a positive influence, even though the statistical effect is not significant. This study highlights that digital learning media such as Nearpod have the potential to enhance student engagement and higher-order thinking skills when implemented consistently and supported by adequate technological infrastructure